2014
DOI: 10.1136/sextrans-2014-051719
|View full text |Cite
|
Sign up to set email alerts
|

The SPORTSMART study: a pilot randomised controlled trial of sexually transmitted infection screening interventions targeting men in football club settings

Abstract: BackgroundUptake of chlamydia screening by men in England has been substantially lower than by women. Non-traditional settings such as sports clubs offer opportunities to widen access. Involving people who are not medically trained to promote screening could optimise acceptability.MethodsWe developed two interventions to explore the acceptability and feasibility of urine-based sexually transmitted infection (STI) screening interventions targeting men in football clubs. We tested these interventions in a pilot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Strategies to increase the reach of these self-taken samples, and thereby lower barriers to accessing STI care for both patients and providers,26 27 include the use of internet-based programmes, e-health strategies and home-collection 28 29…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to increase the reach of these self-taken samples, and thereby lower barriers to accessing STI care for both patients and providers,26 27 include the use of internet-based programmes, e-health strategies and home-collection 28 29…”
Section: Discussionmentioning
confidence: 99%
“…The development and evaluation of the SPORTSMART intervention has been reported elsewhere [ 12 ]. Briefly, we developed two interventions to explore the acceptability and feasibility of urine-based STI (chlamydia and gonorrhoea) screening interventions targeting men in amateur football clubs in London, United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
“…Although healthcare settings may be preferred [ 9 ], previous research suggests that young men are open to STI testing in a range of settings, including non-healthcare settings, such as in sports venues [ 9 11 ]. As such, we developed, piloted, and evaluated two feasible, replicable interventions to promote and deliver STI screening targeting young men in amateur football clubs – ‘SPORTSMART’ [ 12 ]. The hypothesis being that this approach to STI screening may reach men who would not otherwise use sexual health services and could provide a generalisable solution for other health promotion interventions in young men such as drug, smoking, and alcohol awareness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods and results of the pilot trial are reported in detail elsewhere. 5 In brief, a cluster randomised control trial (RCT) design was used involving the allocation of clubs, each with two teams, to one of three trial arms: (1) captain-led and poster STI screening promotion arm; (2) sexual health advisor-led and poster STI screening promotion arm and (3) poster-only STI screening promotion control/comparator arm. The participants were men aged 18 years and over within six amateur football clubs in London.…”
Section: Methodsmentioning
confidence: 99%